2004
DOI: 10.1081/cnv-200039645
|View full text |Cite
|
Sign up to set email alerts
|

Low Overexpression of HER-2/Neu in Advanced Colorectal Cancer Limits the Usefulness of Trastuzumab (Herceptin®) and Irinotecan as Therapy. A Phase II Trial

Abstract: The low overexpression rate of HER-2/neu (8.0%) in advanced CRC limits the potential for further investigation of regimens involving trastuzumab, despite evidence suggestive of activity. Irinotecan did not alter the pharmacokinetic disposition of trastuzumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
76
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(82 citation statements)
references
References 22 publications
(1 reference statement)
1
76
0
1
Order By: Relevance
“…[6][7][8][9][12][13][14][15][16][17][18][19][20] The present study is unique because the only study with an equally large sample size, albeit without clinical validation, reported much lower rates of both ERBB2 expression (2.7%) and positive amplification (1.6%). 8 This difference very likely resides in the fact that while our findings have been obtained on a primarily metastatic population, Heppner et al 8 tested only primary tumors using a different staining antibody (SP3) and a different in situ hybridization method (CISH), and employed gastric cancer criteria to test and score the samples.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[6][7][8][9][12][13][14][15][16][17][18][19][20] The present study is unique because the only study with an equally large sample size, albeit without clinical validation, reported much lower rates of both ERBB2 expression (2.7%) and positive amplification (1.6%). 8 This difference very likely resides in the fact that while our findings have been obtained on a primarily metastatic population, Heppner et al 8 tested only primary tumors using a different staining antibody (SP3) and a different in situ hybridization method (CISH), and employed gastric cancer criteria to test and score the samples.…”
Section: Discussionmentioning
confidence: 97%
“…These are routinely used to establish ERBB2 status in breast and gastric cancer but have not been customized for colorectal cancer for which the reported rate for ERBB2 positivity ranges enormously from o1% to 450%. [6][7][8][9][12][13][14][15][16][17][18][19][20] The aim of the present study was to develop a validated ERBB2 scoring system for colorectal cancer with the goal of identifying ERBB2-positive patients suitable for enrollment in the HERACLES trial.…”
mentioning
confidence: 99%
“…The HER2 protein, a product of HER2 oncogene, is found to be over expressed in some proportion of CRC cells, and seems to be a potentially valid target of interest in the management of colorectal tumors [1,8,19]. One of the main obstacles to conducting relevant studies on HER2 as a predictive and/or prognostic factor is the infrequency of its overexpression in the membrane of CRC cells, which is required for trastuzumab therapy [9,16,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, evidence is emerging that comparative testing of multiple combination strategies in PDXs can be exploited to select for the most effective therapeutic strategy among different options based on a similar rationale (22). For example, the observation obtained in PDXs that a combination of trastuzumab and lapatinib, but not treatment with either drug alone, can induce effective tumor shrinkage of HER2-amplified colorectal cancer is being confirmed in the clinical setting (43); again in line with observations obtained in PDX, trials have failed to demonstrate clinical efficacy of trastuzumab-based regimens in colorectal cancer (55). Similarly, the efficacy of the afatinib/cetuximab combination was effectively predicted by genetically modified mouse models of NSCLC and then confirmed by clinical data (39,56).…”
Section: Discussionmentioning
confidence: 89%